Epicenter Diffusion: Dynamic Network Model - Gámez, R.; Posadas, A.; Luzón, F.; Sotolongo-Costa, O. (Revista Cubana de Física, 2006)
The diffusive behavior of replica secondary earthquakes taking place in Cuba from 1964 to 2000 was determined. Results show that takes place a process of epicenter centralization from the farther points towards the main earthquake impact point. The process is that of an anomalous diffusion in a sub-diffusive regime with exponential constant α = 0.24. It is shown a connection between the probability distribution for localizing the epicenters at a given distance of the main earthquake in the cell with the theoretical results of the Fokker-Planck (EFFP) fractionary equation solution.